BEDİÜZZAMAN SAİD NURSİ’NİN SİYASETE YAKLAŞIMININ DEĞERLENDİRİLMESİ - (:unkn) unknown (My University, 2018)
Bediüzzaman Said Nursi Kürdlerin geri kalmışlığının Osmanlı ve İslam Birliği aleyhinde kullanılma tehlikesine karşı Medresetüzzehra adında Arapça, Kürtçe ve Türkçedillerinde fen ve din ilimlerinin okutulduğu uluslararası bir üniversite tasavvur etmiştir.Eski Said tabir edilen bu dönemde, meşrutiyetle İslam dünyasının esaretten kurtulacağına inanmıştır. Birinci Dünya Savaşı sonlarında Kürdistan tabir edilen Kürdlerin ağırlıklıyaşadığı bölgede Ermeni ve Kürtlerin himayesinde muhtariyet projesine şiddetle karşıçıkmıştır. Muhtariyetin ırkçılık saikıyla istila ve bağımsızlığa yol açacağına ve Kürdlerinbu süreçte maşa olarak kullanılacağına işaret etmiştir. Hilafetin bayraktarı Osmanlılarsayesinde Kürdlerin saadetinin mümkün olduğuna dikkat çekmiştir. Milli Mücadeleyidesteklemekle birlikte laik bir devletin kurulacağını anlayınca fitneye sebep olmamakiçin siyasetten çekilmiştir. Yeni Said dediği bu dönemde yıllarca siyasetten uzak kalmıştır. Sürgünlere, hapishanalere rağmen vatan ve milletin birliği için her türlü baskıyasabretmiştir. Üçüncü Said denilebilecek Çok Partili dönemde vatan, millet ve İslamiyetnoktasında müsbet siyaseti bir araç olarak değerlendirmiştir. Medresettüzzehra, İttihad-ıİslam, Irkçılık tehlikesi, ahkâm ve şeair-i İslam’ın ihyası, Ayasofya’nın açılması, Risalelerin Diyanetce neşri için siyasetçilerle temasa geçmiştir. Özetle bu çalışmada FETÖdarbe girişimiyle din ve siyaset ilişkisinin daha hassas olduğu bir dönemde Nursi’ninsiyaset kavramına, müsbet ve menfi din siyaset ilişkisine yaklaşımı üzerinde durulacaktır.Hayatı siyasetle ilişkisinden hareketle Üç Said şeklinde bütüncül ve karşılaştırmalı birşekilde ele alınacaktır.

Bediüzzaman Said Nursi (1877-1960) imagined an international university based on modern sciences and religious education with Arabic, Kurdish and Turkish languages to prevent abusing of Kurds against Ottoman State and Islamic Union due to of underdevelopment. He thought that Islamic World would release from captivity and underdevelopment by Constitutional Democracy in this era of his life called Old Said. He opposed to the plan of autonomy by jointly sovereignty of Kurd and Armenians in Kurdistan which called a region that most of inhabitants were Kurds. After autonomy, he thought that this would provoke and provide independence and occupation of neighbor borders by using Kurds as an instrument through racism. He pointed out that Kurds peace and pleasure were possible by patronage of Ottoman state which was also the flag of caliphate. In spite of supporting National Independence he left politics when understanding a plan of secular state. He was very far from politics in this era called New Said. He preferred passion despite of exile, prison, oppressions, observation to keep union and peace of country and nation. He looked and used politics as a tool during the era of multi-party period in favour of country, nation, and Islam which may be called Third Said. He began to have contact with politicians by focusing the subjects of Medresetüzzehra, Islamic Union, thread of racism, revival of Islamic symbols and laws, reopening of Hagia Sophia and publication of Risale-i Nur by Turkish Presidency of Religious Affairs. In short, in this study Nursi’s using concept of politics and approaches of positive and negative relationship of politics and religion will be elaborated in the period of sensitive relationship of religion and politics after FETÖ attempt of coup. His life will be taken as three Said periods considering his relationship with politics by searching and comparing holistically all his writings.
An Criticism of Bedıuzzaman Said Nursi’s Approach to Politics
Keywords: Tarih; Dil ve Dil Bilim; Müzik; Din Bilimi